The Effectiveness of Podcast-Based Learning in Enhancing Students’ Listening Skills - Junaidi Rahman (Journal of Practice Learning and Educational Development, 2026)
This study aimed to investigate the effectiveness of podcast-based learning in enhancing students’ listening skills at SMAN 1 Praya. Listening is considered one of the most challenging skills in English language learning because students are required to understand pronunciation, vocabulary, grammar, and meaning simultaneously. Many students experience difficulties in listening comprehension due to limited exposure to authentic English materials and conventional teaching methods. Therefore, podcast-based learning was implemented as an alternative strategy to improve students’ listening competence. This study employed a quantitative approach using a pre-experimental research design with a one-group pre-test and post-test design. The participants consisted of one class of tenth-grade students at SMAN 1 Praya. Data were collected through listening tests, classroom observations, and student interviews. The findings revealed a significant improvement in students’ listening performance after the implementation of podcast-based learning, as indicated by higher post-test scores compared to pre-test scores. Students also demonstrated better ability in identifying main ideas, understanding specific information, recognizing vocabulary in context, and interpreting spoken messages. Furthermore, students showed positive responses toward the use of podcasts because they created a more engaging, flexible, and enjoyable learning environment. Therefore, podcast-based learning can be considered an effective strategy for improving students’ listening skills and motivation in English language learning.